Biochemistry - Ochs, Raymond S.; Ochs, Raymond S. (Burlington, Jone & Bartlet, 2014)
Biochemistry is a single-semester text designed for undergraduate non-biochemistry majors. Accessible, engaging, and informative, Biochemistry is the perfect introduction to the subject for students who may approach chemistry with apprehension. Biochemistry's unique emphasis on metabolism and its kinetic underpinnings gives the text up-to-the-minute relevance for students investigating current public health concerns such as obesity and diabetes. Biochemistry will encourage students to explore the basics of chemistry and its influence on biological problems. Biochemistry provides students with a broad understanding of contemporary advances in molecular biology. Its innovative approach will challenge students to develop connections across multiple concepts, and sets Biochemistry apart in a crowded field. Biochemistry is an invaluable and user-friendly resource. This innovative text for non-biochemistry majors includes: - Introductory material at the beginning of each chapter that contextualizes chapter themes in real-life scenarios - Clear list of objectives for each chapter - Online supporting materials with further opportunities for research and investigation - Synthesis questions at the end of each chapter that encourage students to make connections between concepts and ideas, as well as develop critical-thinking skills
Keywords: Biochemical phenomena; Biochemistry; Botany